A high-stability spiro-OMeTAD hole transport layer and a perovskite solar cell containing the hole transport layer and a preparation method thereof

By doping LiTFSI in the spiro-OMeTAD hole transport layer using supramolecular deep eutectic solvent, the problem of low thermal stability and mechanical stability of LiTFSI dopants at high temperatures in traditional methods is solved, and the pertitanium is significantly improved Stability and photoelectric conversion efficiency of mine solar cells.

CN118354649BActive Publication Date: 2025-02-14NANCHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410499920.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-24
Publication Date
2025-02-14
Estimated Expiration
2044-04-24

AI Technical Summary

Technical Problem

The existing LiTFSI doped spiro-OMeTAD hole transport layer has low thermal stability and mechanical stability at high temperatures, resulting in poor stability of perovskite solar cells and low photoelectric conversion efficiency.

Method used

Doping LiTFSI into spiro-OMeTAD using supramolecular deep eutectic solvent to form a high-stability hole transport layer. By heating and mixing hydrogen bond donor and LiTFSI, it is formed and used with spiro-OMeTAD. The solution is mixed and the precursor liquid is formed and then coated on the substrate surface.

Benefits of technology

Improve the thermal stability and mechanical stability of the spiro-OMeTAD hole transport layer, enhance the overall stability and photoelectric conversion efficiency of perovskite solar cells, and avoid the corrosion of perovskites by acetonitrile and the formation of holes caused by tBP volatilization. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118354649B_ABST
    Figure CN118354649B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of perovskite optoelectronic devices, and discloses a high-stability spiro‑OMeTA D hole transport layer and a perovskite solar cell containing the hole transport layer and a preparation method thereof. The preparation method of the high-stability spiro‑OMeTAD hole transport layer comprises: S1, dissolving spiro‑OMeTAD in a solvent to obtain a spiro‑OMeTAD solution; mixing a hydrogen bond donor and LiTFSI evenly, heating, and obtaining a supramolecular deep eutectic solvent; S2, adding the spiro‑OMeTAD solution to the supramolecular deep eutectic solvent, heating, and obtaining a precursor solution; S3, coating the precursor solution on the surface of a substrate to obtain a high-stability spiro‑OMeTAD hole transport layer. The hole transport layer of the present application avoids the corrosion of the perovskite film by the acetonitrile solvent and the generation of holes in the spiro‑OMeTAD hole transport layer due to the volatilization of tBP at high temperature, and effectively inhibits the Li + By introducing a polymer network into spiro‑OMeTAD, the tensile and fracture resistance of the hole transport layer and its interfacial adhesion with the perovskite light-absorbing layer are improved, thereby improving the stability of the hole transport layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of perovskite optoelectronic devices, and specifically relates to a high-stability spiro-OMe TAD hole transport layer and a perovskite solar cell containing the hole transport layer and a preparation method thereof. Background Art

[0002] Perovskite solar cells have attracted widespread attention due to their low cost, simple preparation process, and high photoelectric conversion efficiency. They have become the photovoltaic technology with the most promising commercial application prospects. Currently, the laboratory-certified efficiency of perovskite cells has reached 26.1%, which shows great potential.

[0003] At present, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) is the most commonly used hole transport material in perovskite solar cells. Due to its low hole mobility, dopants such as lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 4-tert-butylpyridine (tBP) need to be added during the normal preparation of devices to obtain better battery performance. LiTFSI can significantly improve the conductivity and hole mobility of spiro-OMeTAD, while the role of tBP is to assist LiTFSI, making its distribution in spiro-OMeTAD more uniform, regulating the morphology of the hole transport layer, and inhibiting carrier recombination.

[0004] However, LiTFSI is extremely easy to migrate at high temperatures, while tBP is easy to volatilize and leave holes, which reduces the thermal stability of the hole transport layer and flexible solar cells. At the same time, the solvent acetonitrile is required in the LiTFSI doping process, which will corrode the perovskite and cause the flexible perovskite solar cell to degrade; in addition, spiro-OMeTAD, as a small molecule, has a very low fracture energy and is easy to break under the mechanical stress generated during the degradation of the perovskite solar cell. It is also easy to cause the contact surface with the perovskite to harden during the operation of the device, resulting in a decrease in the adhesion between the spiro-OMeTAD / perovskite interface and a reduction in the mechanical stability of the flexible perovskite solar cell. The above results in poor stability of flexible perovskite solar cells, limiting their wide application. Summary of the invention

[0005] The present application provides a high-stability spiro-OMeTAD hole transport layer and a perovskite solar cell containing the hole transport layer and a preparation method thereof, aiming to solve the problem that the existing LiTFSI-doped spiro-OMeTAD hole transport layer has low thermal stability and mechanical stability, which in turn leads to poor stability and low photoelectric conversion efficiency of perovskite solar cells.

[0006] In order to achieve the above objectives, the present application adopts the following technical solutions.

[0007] In a first aspect of the present application, a method for preparing a high-stability spiro-OMeTAD hole transport layer is provided, comprising:

[0008] S1, dissolving spiro-OMeTAD in a solvent to obtain a spiro-OMeTAD solution; mixing the hydrogen bond donor and LiTFSI evenly, and heating to obtain a supramolecular deep eutectic solvent;

[0009] S2, adding the spiro-OMeTAD solution into the supramolecular deep eutectic solvent and heating to obtain a precursor solution;

[0010] S3, coating the precursor solution on the surface of the substrate to obtain a high-stability spiro-OMeTAD hole transport layer.

[0011] In some embodiments, the solvent is chlorobenzene, o-xylene, or chloroform.

[0012] In some embodiments, the hydrogen bond donor is an amide compound or an imidazole compound.

[0013] In some embodiments, the molar concentration of the spiro-OMeTAD solution is 0.049-0.073 mol / mL.

[0014] In some embodiments, the molar ratio of the hydrogen bond donor to LiTFSI is 6:4 to 9:1.

[0015] In some embodiments, the heating temperature in step S1 is 70-90°C; and the heating temperature in step S2 is 50-60°C.

[0016] In another aspect of the present application, a high-stability spiro-OMeTAD hole transport layer prepared by the above preparation method is provided.

[0017] In another aspect of the present application, a perovskite solar cell is provided, comprising a transparent conductive substrate, an electron transport layer, a perovskite light absorption layer, a high-stability spiro-OMeTAD hole transport layer, and a metal electrode;

[0018] Among them, the thickness of the transparent conductive substrate is 10nm-500nm; the thickness of the electron transport layer is 10nm-400nm; the thickness of the perovskite light absorption layer is 10nm~800nm; the thickness of the high-stability spiro-OMeTAD hole transport layer is 10nm-400nm.

[0019] In some embodiments, the transparent conductive substrate is FTO or ITO;

[0020] The electron transport layer is prepared from any one or more combinations of tin dioxide, titanium dioxide or zinc oxide;

[0021] The perovskite light absorbing layer is FA, FAMA or FAMACs type perovskite;

[0022] The metal electrode is gold or silver.

[0023] Another aspect of the present application provides a method for preparing the above-mentioned perovskite solar cell, comprising:

[0024] S1, etching the transparent conductive substrate and cleaning it;

[0025] S2, depositing an electron transport layer on the cleaned transparent conductive substrate;

[0026] S3, depositing a perovskite film on the electron transport layer as a perovskite light absorbing layer;

[0027] S4, depositing a high-stability spiro-OMeTAD hole transport layer on the surface of the perovskite light-absorbing layer;

[0028] S5, evaporating a metal electrode to obtain a perovskite solar cell.

[0029] Compared with the prior art, the beneficial effects of this application are:

[0030] This application uses a supramolecular deep eutectic solvent to dope LiTFSI into spiro-OMeTAD to obtain a highly stable spiro-OMeTAD hole transport layer. The hole transport layer of this application does not require acetonitrile and tBP. On the one hand, it avoids the corrosion of the perovskite film by the acetonitrile solvent, reduces the defects on the surface of the perovskite light absorption layer, and improves the carrier transmission effect; on the other hand, it avoids the generation of holes in the spiro-OMeTAD hole transport layer due to the volatilization of tBP at high temperature. In addition, there is a strong molecular force between the supramolecular deep eutectic solvent and LiTFSI, which effectively inhibits the Li + The above together improve the thermal stability of the hole transport layer, as well as the thermal stability and photoelectric conversion efficiency of the flexible perovskite solar cell.

[0031] The present application introduces a polymer network into spiro-OMeTAD through a supramolecular deep eutectic solvent, thereby improving the tensile and fracture resistance of the spiro-OMeTAD hole transport layer and the interfacial adhesion of the spiro-OMeTAD hole transport layer with the perovskite light absorption layer and the electrode, thereby improving the mechanical stability of the hole transport layer and the flexible perovskite solar cell and enabling it to have self-healing ability.

[0032] The preparation method of the present application is relatively simple and easy to operate, and is applicable to the preparation of various perovskite systems and various perovskites. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0034] Figure 1 A schematic diagram of the structure of a perovskite solar cell provided in this application;

[0035] Figure 2 The morphology of the hole transport layer film provided in Example 1 and Comparative Example 1 observed with an optical microscope before and after bending;

[0036] Figure 3 Young's modulus test graph and statistical graph of the hole transport layer film provided in Example 1 and Comparative Example 1;

[0037] Figure 4 The photoelectric performance data of the perovskite solar cells prepared in Example 6 and Comparative Example 2 are shown in FIG.

[0038] Figure 5 The photoelectric performance data of the perovskite solar cells prepared in Example 7 and Comparative Example 2 are shown in FIG.

[0039] Figure 6 The photoelectric conversion efficiency data of the perovskite solar cells prepared in Example 6 and Comparative Example 2 after bending are shown;

[0040] Figure 7 This is a data graph of the photoelectric conversion efficiency of the perovskite solar cells prepared in Example 6 and Comparative Example 2 at 85°C. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0042] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.

[0043] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0044] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0045] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0046] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0047] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be understood as each intermediate value between the upper and lower limits of the scope also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.

[0048] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0049] In a first aspect, the present application provides a method for preparing a high-stability spiro-OMeTAD hole transport layer, comprising:

[0050] S1, dissolving spiro-OMeTAD in a solvent to obtain a spiro-OMeTAD solution; mixing the hydrogen bond donor and LiTFSI evenly, and heating to obtain a supramolecular deep eutectic solvent;

[0051] S2, adding the spiro-OMeTAD solution into the supramolecular deep eutectic solvent and heating to obtain a precursor solution;

[0052] S3, coating the precursor solution on the surface of the substrate to obtain a high-stability spiro-OMeTAD hole transport layer.

[0053] In the present application, the substrate may be a perovskite light absorbing layer, a transparent conductive substrate such as a FTO conductive layer or an ITO conductive layer, and a flexible substrate.

[0054] In the present application, the solvent is used to dissolve spiro-OMeTAD to make the spiro-OMeTAD uniformly dispersed; the solvent can be chlorobenzene, o-xylene or chloroform, but is not limited to the above organic substances.

[0055] In the present application, the hydrogen bond donor is an amide compound or an imidazole compound. Specifically, the amide compound can be N-cyanomethylacetamide or N-cyanomethylacrylamide, and the imidazole compound can be 1,2-dimethylimidazole or 1-vinylimidazole.

[0056] In this application, LiTFSI is used as a hydrogen bond acceptor, and a hydrogen bond donor molecule is introduced into the hydrogen bond acceptor LiTFSI, and a supramolecular deep eutectic solvent is formed by heating. The supramolecular deep eutectic solvent is dissolved in the spiro-OMeTAD solution to form a precursor solution, and the precursor solution is coated on the surface of the perovskite film to obtain a high-stability spiro-OMeTAD hole transport layer. Among them, DES has the advantages of excellent tensile and fracture resistance, high adhesion, low vapor pressure, good self-healing ability, etc., and the strong interaction between molecules in DES effectively inhibits Li + Migration and improving the self-healing ability of spiro-OMeTAD; and using DES to introduce LiTFSI into spiro-OMeTAD to replace acetonitrile and tBP, thereby avoiding the corrosion of acetonitrile to perovskite and the volatilization of tBP at high temperature and destroying the hole transport layer structure; at the same time, the polymer network and high adhesion in DES can improve the mechanical toughness and interfacial adhesion of spiro-OMeTAD, thereby effectively improving the thermal stability and mechanical stability of the obtained spiro-OMeTAD.

[0057] In the embodiments of the present application, the molar concentration of the spiro-OMeTAD solution is 0.049-0.073 mol / mL; the molar ratio of the hydrogen bond donor to LiTFSI is 6:4 to 9:1. The present application selects the above molar concentration and the above molar ratio, and the prepared precursor solution is coated on the surface of the perovskite film without heating or other treatment, and a spiro-OMeTAD film can be spontaneously formed, which has good mechanical toughness and interface adhesion.

[0058] In the present application, when the hydrogen bond donor and LiTFSI are uniformly mixed to prepare the supramolecular deep eutectic solvent, the heating temperature is selected to be 70-90° C., preferably 80° C. By selecting the above temperature range, the distribution of the supramolecular deep eutectic solvent components can be made more uniform.

[0059] The spiro-OMeTAD solution is added to the supramolecular deep eutectic solvent, and when preparing the precursor solution, the heating temperature is selected to be 50-60° C., preferably 50° C. By selecting the above temperature range, the spiro-OMeTAD in the precursor solution can be more evenly distributed, thereby improving its deposition effect on the perovskite film.

[0060] In a second aspect, the present application provides a high-stability spiro-OMeTAD hole transport layer prepared by the above method. The high-stability spiro-OMeTAD hole transport layer is free of acetonitrile and tBP, has low corrosiveness to perovskite films, and has high mechanical stability and interface adhesion.

[0061] In a third aspect, the present application provides a perovskite solar cell, comprising a transparent conductive substrate, an electron transport layer, a perovskite light absorption layer, a high-stability spiro-OMeTAD hole transport layer prepared in the present application, and a metal electrode. The perovskite solar cell may be a NIP structure or a PIN structure, wherein the thickness of the transparent conductive substrate is 10nm-500nm; the thickness of the electron transport layer is 10nm-400nm; the thickness of the perovskite light absorption layer is 10nm-800nm; and the thickness of the high-stability spiro-OMeTAD hole transport layer is 10nm-400nm.

[0062] The perovskite solar cell prepared in the present application reduces surface defects, improves the molecular stacking of spiro-OMeTAD, is beneficial to the transmission of carriers, and has higher photoelectric conversion efficiency and higher stability.

[0063] In the perovskite solar cell of the present application, the transparent conductive substrate may be FTO or ITO; the transparent conductive substrate may be a flexible transparent conductive substrate or a rigid transparent conductive substrate.

[0064] The electron transport layer can be prepared from any one or more combinations of tin dioxide, titanium dioxide or zinc oxide; it should be noted that the raw materials of the electron transport layer include but are not limited to the above raw materials. The perovskite light absorption layer can be FA, FAMA or FAMACs type perovskite; the metal electrode includes but is not limited to gold or silver.

[0065] The present application is further described below by way of examples. In the following examples:

[0066] spiro-OMeTAD is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene;

[0067] A-DES is a supramolecular deep eutectic solvent;

[0068] LiTFSI is lithium bis(trifluoromethanesulfonyl)imide;

[0069] tBP is 4-tert-butylpyridine;

[0070] DMF is N,N-dimethylformamide;

[0071] DMSO is dimethyl sulfoxide;

[0072] FAI is formamidine iodide;

[0073] MAI is methylamine iodide;

[0074] MACl is methylammonium chloride.

[0075] Example 1

[0076] This embodiment provides a method for preparing a high-stability spiro-OMeTAD hole transport layer, comprising:

[0077] S1, dissolving 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene to prepare a spiro-OMeTAD solution with a concentration of 0.06 mol / L; mixing 0.073 mol of N-cyanomethylacetamide and 0.032 mol of LiTFSI, and heating at 80°C for 20 min to obtain A-DES;

[0078] S2, adding spiro-OMeTAD solution into A-DES and heating at 50 °C for 2 h to obtain a precursor solution;

[0079] S3, drop the precursor onto the surface of the flexible substrate and spin coat it at 4000 rpm for 30 s to obtain a highly stable spiro-OMeTAD hole transport layer film.

[0080] Example 2

[0081] This embodiment provides a method for preparing a high-stability spiro-OMeTAD hole transport layer, comprising:

[0082] S1, dissolving 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene to prepare a spiro-OMeTAD solution with a concentration of 0.06 mol / L; mixing 0.06 mol of N-cyanomethylacetamide and 0.04 mol of Li TFSI, and heating at 80°C for 20 min to obtain A-DES;

[0083] S2, adding spiro-OMeTAD solution into A-DES and heating at 50 °C for 2 h to obtain a precursor solution;

[0084] S3, drop the precursor onto the surface of the flexible substrate and spin coat it at 4000 rpm for 30 s to obtain a highly stable spiro-OMeTAD hole transport layer film.

[0085] Example 3

[0086] This embodiment provides a method for preparing a high-stability spiro-OMeTAD hole transport layer, comprising:

[0087] S1, dissolving 89 mg of spiro-OMeTAD in 1 mL of chlorobenzene to prepare a spiro-OMeTAD solution with a concentration of 0.073 mol / L; mixing 0.09 mol of N-cyanomethyl acrylamide and 0.01 mol of LiTFSI, and heating at 90°C for 20 min to obtain A-DES;

[0088] S2, adding spiro-OMeTAD solution into A-DES and heating at 50 °C for 2 h to obtain a precursor solution;

[0089] S3, drop the precursor onto the surface of the flexible substrate and spin coat it at 4000 rpm for 30 s to obtain a highly stable spiro-OMeTAD hole transport layer film.

[0090] Example 4

[0091] This embodiment provides a method for preparing a high-stability spiro-OMeTAD hole transport layer, comprising:

[0092] S1, dissolving 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene to prepare a spiro-OMeTAD solution with a concentration of 0.06 mol / L; mixing 0.073 mol of 1,2-dimethylimidazole and 0.032 mol of Li TFSI, and heating at 80 °C for 20 min to obtain A-DES;

[0093] S2, adding spiro-OMeTAD solution into A-DES and heating at 50 °C for 2 h to obtain a precursor solution;

[0094] S3, drop the precursor onto the surface of the flexible substrate and spin coat it at 4000 rpm for 30 s to obtain a highly stable spiro-OMeTAD hole transport layer film.

[0095] Example 5

[0096] This embodiment provides a method for preparing a high-stability spiro-OMeTAD hole transport layer, comprising:

[0097] S1, dissolving 60 mg of spiro-OMeTAD in 1 mL of chlorobenzene to prepare a spiro-OMeTAD solution with a concentration of 0.049 mol / L; mixing 1,2-dimethylimidazole and LiTFSI in a molar ratio of 7:3, and heating at 80°C for 20 min to obtain A-DES;

[0098] S2, adding spiro-OMeTAD solution into A-DES and heating at 60 °C for 2 h to obtain a precursor solution;

[0099] S3, drop the precursor onto the surface of the flexible substrate and spin coat it at 4000 rpm for 30 s to obtain a highly stable spiro-OMeTAD hole transport layer film.

[0100] Comparative Example 1

[0101] This comparative example provides a method for preparing an existing spiro-OMeTAD hole transport layer, comprising:

[0102] Dissolve 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene to prepare a spiro-OMeTAD solution with a concentration of 0.06 mol / L;

[0103] Dissolve LiTFSI in acetonitrile to prepare a LiTFSI acetonitrile solution with a concentration of 520 mg / mL;

[0104] Add 17.5 μL of LiTFSI acetonitrile solution to 1 mL of spiro-OMeTAD solution, then add 28.85 μL of tBP, mix and fully dissolve to obtain a precursor solution;

[0105] The precursor liquid was dropped onto the surface of the flexible substrate and spin coated at 4000 rpm for 30 s to obtain a spiro-OMeTAD hole transport layer film.

[0106] The performance of the hole transport layer prepared in Example 1 and Comparative Example 1 was evaluated as follows:

[0107] The hole transport layer films prepared in Example 1 and Comparative Example 1 were taken and bent 5000 times. The two hole transport layer films were observed with an optical microscope before and after bending. The morphology is shown in the figure below. Figure 2 shown.

[0108] Figure 2 In the figure, (a) is a morphological diagram of the hole transport layer film of comparative example 1 before bending; (b) is a morphological diagram of the hole transport layer film of comparative example 1 after bending 5000 times; (c) is a morphological diagram of the hole transport layer film of embodiment 1 before bending; (d) is a morphological diagram of the hole transport layer film of embodiment 1 after bending 5000 times. Figure 2 It can be seen that the hole transport layer film of Example 1 did not produce any cracks after being bent 5000 times, while the hole transport layer film of Comparative Example 1 produced obvious cracks after being bent 5000 times. The mechanical stability of the hole transport layer film prepared in Example 1 is significantly improved, which is because the deep eutectic solvent has excellent tensile and fracture resistance mechanical properties, and the polymer network in the deep eutectic solvent increases the mechanical stability and self-healing ability of the spiro-OMeTAD hole transport layer.

[0109] The hole transport layer films prepared in Example 1 and Comparative Example 1 were respectively taken to test their Young's modulus. The test results and statistical graphs are shown in FIG. Figure 3 As shown. Figure 3 As can be seen from (c) and (a), compared with Comparative Example 1, the hole transport layer film prepared in Example 1 has a smaller Young's modulus and better flexibility. Figure 3 From (d) and (b), it can be seen that the hole transport layer film prepared in Example 1 is more uniform.

[0110] Example 6

[0111] This embodiment provides a method for preparing a perovskite cell including a high-stability spiro-OMeTAD hole transport layer, comprising:

[0112] S1, a 2.5 cm × 2.5 cm etched ITO conductive glass substrate was combined with a flexible substrate polyethylene naphthalate (PEN), and then cleaned by ultrasonic treatment in detergent, acetone, deionized water, and isopropanol for 15 min. Then, it was dried with N2 and placed in a plasma cleaner to treat the ITO substrate with UV-ozone for 10 min;

[0113] S2, spin coating SnO2 (2.67 wt% aqueous solution) on the surface of the ITO conductive glass substrate at a speed of 3000 rpm for 30 s, and thermally annealing at 150°C in air for 30 min to obtain a SnO2 electron transport layer;

[0114] S3, prepare lead iodide precursor solution: weigh 1.5mmol PbI2 and dissolve it in 1mL DMF:DMSO=95:5 solvent, heat on a hot plate at 60℃ overnight for later use.

[0115] Prepare organic ammonium salt solution: dissolve 90 mg FAI, 6.9 mg MAI and 9 mg MACl in 1 mL isopropanol, then place in a shaker to fully dissolve and set aside.

[0116] An appropriate amount of lead iodide precursor solution was spin-coated onto the SnO2 electron transport layer at a speed of 1500 rpm for 30 seconds, and a lead iodide film was obtained after the first annealing treatment;

[0117] An organic ammonium salt solution was spin-coated on the lead iodide film at a rotation speed of 2000 rpm for 30 seconds, and a perovskite light-absorbing layer was obtained after a second annealing treatment.

[0118] S4, prepare spiro-OMeTAD solution: weigh 72.3 mg of spiro-OMeTAD powder and dissolve it in 1 mL of chlorobenzene. Place it on a shaker to fully dissolve and set aside.

[0119] Prepare an amide deep eutectic solvent: mix 0.073 mol of N-cyanomethylacetamide and 0.032 mol of LiTFSI evenly, and heat at 80° C. for 20 min to obtain A-DES for later use.

[0120] The spiro-OMeTAD solution was mixed with A-DES and heated at 50 °C for 2 h to obtain a precursor solution;

[0121] Take an appropriate amount of precursor droplets on the surface of the perovskite light-absorbing layer, spin-coat at a speed of 4000 rpm for 30 seconds to obtain a highly stable spiro-OMeTAD hole transport layer film.

[0122] S5, placing the product obtained in step S4 in an evaporator, evaporating Ag on the surface of the hole transport layer under high vacuum to obtain a metal electrode Ag, and obtaining a perovskite solar cell, the structure of which is as follows Figure 1 shown.

[0123] Example 7

[0124] This embodiment provides a method for preparing a perovskite cell including a high-stability spiro-OMeTAD hole transport layer. The difference between this method and Example 6 is that N-cyanomethylacetamide in step S4 is replaced by 1,2-dimethylimidazole, and the rest is the same as Example 6.

[0125] Comparative Example 2

[0126] Comparative Example 2 provides a method for preparing a perovskite cell comprising a spiro-OMeTAD hole transport layer. The difference between Comparative Example 2 and Examples 6 and 7 is that step S4 is different.

[0127] Step S4 of Comparative Example 2 is:

[0128] Dissolve 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene to prepare a spiro-OMeTAD solution with a concentration of 0.06 mol / L;

[0129] Dissolve LiTFSI in acetonitrile to prepare a LiTFSI acetonitrile solution with a concentration of 520 mg / mL;

[0130] Add 17.5 μL of LiTFSI acetonitrile solution to 1 mL of spiro-OMeTAD solution, then add 28.85 μL of tBP, mix and fully dissolve to obtain a precursor solution;

[0131] The precursor liquid was dropped onto the surface of the perovskite light-absorbing layer and spin-coated at 4000 rpm for 30 seconds to obtain a spir o-OMeTAD hole transport layer film.

[0132] The photoelectric performance of the perovskite cells prepared in Example 6, Example 7 and Comparative Example 2 was tested. The test data are shown in Table 1. The current-voltage characteristic curves are shown in Table 1. Figure 4 , Figure 5 shown.

[0133]

[0134]

[0135] From Table 1 and Figure 4 , Figure 5 It can be seen that the perovskite solar cells prepared in Example 6, Example 7 and Comparative Example 2 have a photoelectric conversion efficiency of 21.22% in Example 6, 21.09% in Example 7, and 18.59% in Comparative Example 2. The photoelectric conversion efficiency of the perovskite solar cells in Example 6 and Example 7 is significantly higher than that in Comparative Example 2. In the perovskite solar cells in Example 6 and Example 7, the hole transport layer introduces a supramolecular deep eutectic solvent instead of acetonitrile and tBP, which avoids the corrosion of the surface of the perovskite light absorption layer by acetonitrile and tBP, and effectively reduces the Li + Migration reduces the defects on the surface of the perovskite light-absorbing layer, improves the transmission effect of carriers, and thus improves the photoelectric conversion efficiency.

[0136] The perovskite solar cells prepared in Example 6 and Comparative Example 2 were bent 5000 times and their photoelectric conversion efficiency was tested. The test results are as follows: Figure 6 As shown, under the same bending conditions, Example 6 exhibits excellent bending stability, maintaining 93% of the initial efficiency after 5000 cycles, while Comparative Example 2 only maintains 27% of the initial efficiency. The results show that the spiro-OMeTAD hole transport layer introduced with supramolecular deep eutectic solvent has higher tensile and fracture resistance, interface adhesion and self-healing ability, thereby improving the mechanical bending resistance of flexible perovskite solar cells, and still has a high photoelectric conversion efficiency after 5000 bends.

[0137] The perovskite solar cells prepared in Example 6 and Comparative Example 2 were subjected to a thermal stability test at 85°C. The test results are shown in FIG. Figure 7 As shown. Under the same bending conditions, Example 6 exhibits excellent high temperature stability and maintains 90% of the initial efficiency after being heated at 85°C for more than 2000 hours, while Comparative Example 2 only maintains 20% of the initial efficiency. The results show that the spiro-OMeTAD hole transport layer introduced with the supramolecular deep eutectic solvent has higher thermal stability, thereby improving the high temperature bending performance of the flexible perovskite solar cell, and still has a high photoelectric conversion efficiency after being heated at 85°C for more than 2000 hours.

[0138] Although the present application has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present application. Therefore, these modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in the present application.

Claims

1. A method for preparing a high-stability spiro-OMeTAD hole transport layer, characterized in that: include: S1, dissolving spiro-OMeTAD in a solvent to obtain a spiro-OMeTAD solution; mixing the hydrogen bond donor and LiTFSI evenly, and heating to obtain a supramolecular deep eutectic solvent; S2, adding the spiro-OMeTAD solution into the supramolecular deep eutectic solvent and heating to obtain a precursor solution; S3, coating the precursor solution on the surface of the substrate to obtain a high-stability spiro-OMeTAD hole transport layer; Wherein, the hydrogen bond donor is N-cyanomethylacetamide, N-cyanomethylacrylamide, 1,2-dimethylimidazole or 1-vinylimidazole; The molar ratio of the hydrogen bond donor to LiTFSI is 6:4 to 9:

1.

2. The method for preparing a high-stability spiro-OMeTAD hole transport layer according to claim 1, characterized in that: The solvent is chlorobenzene, o-xylene or chloroform.

3. The method for preparing a high-stability spiro-OMeTAD hole transport layer according to claim 1 or 2, characterized in that: The molar concentration of the spiro-OMeTAD solution is 0.049-0.073 mol / mL.

4. The method for preparing a high-stability spiro-OMeTAD hole transport layer according to claim 1, characterized in that: The heating temperature in step S1 is 70-90°C; The heating temperature in step S2 is 50-60°C.

5. A high-stability spiro-OMeTAD hole transport layer prepared by the method for preparing a high-stability spiro-OMeTAD hole transport layer according to any one of claims 1 to 4.

6. A perovskite solar cell, characterized in that: It comprises a transparent conductive substrate, an electron transport layer, a perovskite light absorption layer, the high-stability spiro-OMeTAD hole transport layer as claimed in claim 5, and a metal electrode; Among them, the thickness of the transparent conductive substrate is 10nm-500nm; the thickness of the electron transport layer is 10nm-400nm; the thickness of the perovskite light absorption layer is 10nm~800nm; the thickness of the high-stability spiro-OMeTAD hole transport layer is 10nm-400nm.

7. The perovskite solar cell according to claim 6, characterized in that: The transparent conductive substrate is FTO or ITO; The electron transport layer is prepared from any one or more combinations of tin dioxide, titanium dioxide or zinc oxide; The perovskite light absorbing layer is FA, FAMA or FAMACs type perovskite; The metal electrode is gold or silver.

8. The method for preparing a perovskite solar cell according to claim 6 or 7, characterized in that: include: S1, etching the transparent conductive substrate and cleaning it; S2, depositing an electron transport layer on the cleaned transparent conductive substrate; S3, depositing a perovskite film on the electron transport layer as a perovskite light absorbing layer; S4, depositing a high-stability spiro-OMeTAD hole transport layer on the surface of the perovskite light-absorbing layer; S5, evaporating a metal electrode to obtain a perovskite solar cell.